The lung : development, aging and the environment - Harding, Richard, 1944-; Pinkerton, Kent Ed, 1950-; Plopper, Charles G. (Elsevier Academic Press, 2004)
This unique book provides a concise account, written by world authorities in their fields, of how the mammalian lung grows and matures before birth and how the lungs, and their ability to function well, can be affected by the environment and by genetic factors, both before and after birth. It provides an understanding of the basis of some major lung diseases affecting infants and children. The book also deals with how the lung changes with age, and how the process of lung aging can be affected by the environment. * Discusses the mechanisms that regulate th.